Iran’s Past Future: A Critique on the Book Iranian Ministry and Bureaucracy (Vezarat & Divansalari) in the Islamic Era - Morteza Bahrani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The future of Iran’s history largely depends on narratives we present from its past. The narratives can lead to freedom and responsibility, or they can impose a kind of retrospective on us that prevents us from progressing. Depending on what approach and values we have in mind, Iran's past will also be different. In this article, by reviewing Iranian Ministry and Bureaucracy (Vezarat & Divansalari) in the Islamic Era (written by Sadeq Sajjadi), I have critiqued our vicious history with regard to the author's approach to validation of the past, and have expressed some critical arguments in a suspicious hermeneutic method. In my opinion, the future of Iran’s progress is first and foremost dependent on the deconstruction of its bureaucratic (Divansalari) relations. This bureaucracy, instead of order and efficiency, and transparency, leads to obscurity. This is the future that is a searchlight for, and the beacon of the past.